Viral suppression and mortality among HIV infected adults initiated Anti-Retroviral Therapy at Temeke Regional hospital: Programmatic achievements and Opportunities for improvement (Tanzania Medical Journal, 2020)
BackgroundDespite the fact that HIV disease has greater impact in the Sub-Saharan Africa (SSA) region, treatment outcomes are scarcely reported at implementation level. Programmatic data present real life implementation challenges of public health importance which should inform policies. This study was conducted to describe mortality, viral suppression and document challenges at secondary facility HIV clinic in Temeke, Dar es Salaam Tanzania.MethodsHospital-based retrospective cohort study was conducted among HIV patients initiated on ART between May and November 2016 at Temeke Hospital, Dar es Salaam, Tanzania. Data was collected from HIV database between May and November 2017. Mortality was reported as proportion while viral suppression was defined as HIV-RNA below 50 copies per ml.ResultsA total of 747 PLHIV were eligible and were included in the study. Out of these, forty (5.4) patients died. Good adherence to Antiretroviral therapy was seen in 70% of PLHV only. Of the 419 participants with HIV viral load measurements, viral suppression was achieved in 318 (75.9%) patients. Viral suppression is more likely for patients with CD4+ T lymphocyte count greater than 200 cells/µL. There was high attrition rate from the clinic, more than one-third 35.2% of those initiated ART were still attending the clinic at one year.ConclusionHIV viral suppression and adherence to ART at Temeke HIV CTC are still sub-optimal. Good tracking, enhanced adherence as well as early diagnosis and treatment might improve viral suppression at one year. High attrition from the clinic may need careful examination.Keywords: Viral suppression, HIV, SSA, treatment failure, AIDS, Tanzania